Hegemony as a stabilizing factor of the international/global system and order - Murillo Zamora, Carlos (2025)
Hegemony is examined as stabilizing factor of the international system and the international/global order. It is argued that the stability of an international system is achieved through it, whether by a global hegemon or several regional hegemons, rather than by a balance of power. Order is defined as the structure of relations between states and other actors, based on norms and agreements that regulate their behavior. Hegemony refers to the ability of a powerful state to influence and shape behavior without direct dominance, utilizing its military, economic, and cultural power.The international/global order is conceptualized as the structure of the relationships and links that exist between states and other international actors in the system, which is based on the norms, rules, and agreements regulating the conduct of the actors. It is related to systemic stability and predictability in international relations. Therefore, it describes how associations between different international actors, primarily state actors, are organized and regulated.The text also analyzes how hegemonic powers, such as the United States, China, and Russia, influence the international system through various hegemonic projects based on their worldviews. It is highlighted that the international system is undergoing a “profound transformation,” marked by a diminished role of the nation-state and a growing technological revolution. Small states can maneuver against hegemonic powers through strategies such as forming alliances and taking advantage of competition among great powers.